Consumers' Intention to Attend Soccer Events: Application and Extension of the Theory of Planned Behavior. Issue 1 (August 2015) - Eddosary, Melfy; Ko, Yong Jae; Sagas, Michael; Kim, Hee Youn
The purpose of this study was to identify important factors of consumers' intention to attend professional soccer events among Saudi Arabian soccer fans. To explore the decision-making process of this relatively understudied population, the theory of planned behavior was used as theoretical background. Particularly, this study measured the effect of attitude, subjective norm, perceived behavioral control (time and money), and game importance on intention to attend, and examined the moderating role of commitment. Structural equation modeling (SEM) using 231 Saudi university students ( M = 21.9 yr., SD = 1.21) indicate that attitude and game importance were significantly related to attendance intention. The effect of subjective norms was significant only for the low commitment group and game importance was more important for the low than the high commitment group.